Evaluation of Anticoagulant Use in Post Valvular Heart Surgery in Relation with International Normalised Ratio (INR) and Valve Replaced - Soni, Pawan; Panda, Khushi; Joseph, Jishi Joshi; Gaur, Kalpesh; Gandhi, Sanjay; Rathore, Mahendra Singh (Indian Journal of Pharmacy Practice)
Background: Valvular heart disease is a growing concern worldwide. Patients diagnosed with valvular heart disease are majorly indicated for valve replacement or repair surgery which may lead to thromboembolic events. To prevent these thromboembolic events anticoagulants and antiplatelets are usually prescribed, but use of these agents on the other hand may lead to bleeding events, hence optimal INR range needs to be maintained. Purpose: Our study aimed to analyze the optimal INR range for patients with different types of valve replacements and to assess use of anticoagulants in patients after valve replacement. Materials and Methods: This study is a prospective, observational with a total sample size of 108 who underwent valve replacement were considered. Pre-designed data collection forms were used to collect specific data. All parameters were categorized into continuous variables and categorical variables and were then evaluated. Results: Out of 108 patients 45 were males 63 were females with mean age of 43.87±15.94. A total of 58% patients had problem associated with mitral valve and 22% had problems with aortic valve. Rest came with complaints in multiple valve. Out of 108 patients 100 (92%) patients were indicated for mechanical valve implant and 08 (8%) patients were indicated for tissue valve implant. All 108 patients were given with acitrom as an anticoagulants with varying daily doses depending on their daily INR values. Optimal INR range varied based on type of valve affected and type of valve implanted and was found to be statistically significant (p=0.0023). Out of 108 patients 96 (89%) were given with antiplatelet agent (aspirin) along with anticoagulants and 12 (11%) were not given with antiplatelet agent due to increased risk of bleeding. Conclusion: From the present study it is evident that the most common valve affected was mitral valve with varying pathology of stenosis, regurgitation and combination of both. Mechanical valve was used more in comparision to prosthetic valves for valve replacement. Anticoagulation is necessary along with use of antiplatelet agent to prevent thromboembolic events in post valvular surgery. INR values to be maintained varied based on type of valve replaced, mechanical valves required maintenance of higher INR value because of increased risk of thromboembolic events.
Keywords: Valvular heart surgery; INR; Vitamin K antagonist; Antiplatelet agent; Bioprosthetic valve; Mechanical valve.